PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA TOKO AN NUR - Liansari, Denik Nureta; Samari; Sardanto, Rino (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to determine and analyze how the influence of product quality, service quality and price on consumer satisfaction at An Nur Stores. The study was conducted using a quantitative approach with the causality method, with primary data from research questionnaires given to 40 respondents according to the criteria. The data analysis technique used is validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis test including t test and f test, and coefficient of determination with the help of SPSSv23. The results of this study indicate that product quality has a positive effect on consumer satisfaction, service quality has a positive effect on consumer satisfaction, and price has a negative effect on consumer satisfaction, while product quality, service quality and price simultaneously affect consumer satisfaction.